1995
DOI: 10.1038/374287a0
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific RNase E cleavage of oligonucleotides and inhibition by stem–loops

Abstract: The enzyme RNase E (ref. 1) cuts RNA at specific sites within single-stranded segments. The role of adjacent regions of secondary structure in such cleavages is controversial. Here we report that 10-13-nucleotide oligomers lacking any stem-loop but containing the RNase E-cleaved sequence of RNA I, the antisense repressor of replication of ColE1-type plasmids, are cut at the same phosphodiester bond as, and 20 times more efficiently than, RNA I. These findings indicate that, contrary to previous proposals, stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
153
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(156 citation statements)
references
References 22 publications
2
153
1
Order By: Relevance
“…Note that in this region the eight-base sequence, AAUUAUUA, from bases 139-146, is in a single-stranded region in a bulge. This sequence may be an RNase E cleavage site as defined as an AU-rich region flanked by stable secondary structures (Naureckiene and Uhlin, 1996), although the requirement of secondary structures for RNase E cleavage is dependent upon its substrate structures (McDowall et al, 1995). It is important to note that a two-base substitution mutation from UAUUA to UUCUA by itself stabilized the mRNA at most by twofold, and, similarly, that the A to G mutation at base 147 also stabilized the mRNA only by 10-fold.…”
Section: Discussionmentioning
confidence: 99%
“…Note that in this region the eight-base sequence, AAUUAUUA, from bases 139-146, is in a single-stranded region in a bulge. This sequence may be an RNase E cleavage site as defined as an AU-rich region flanked by stable secondary structures (Naureckiene and Uhlin, 1996), although the requirement of secondary structures for RNase E cleavage is dependent upon its substrate structures (McDowall et al, 1995). It is important to note that a two-base substitution mutation from UAUUA to UUCUA by itself stabilized the mRNA at most by twofold, and, similarly, that the A to G mutation at base 147 also stabilized the mRNA only by 10-fold.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Fig. 2, panel A, a 5-nucleotide 3Ј-(Fl)-labeled fragment produced by hydrolysis of p-BR10-Fl, a 10-nucleotide substrate corresponding in sequence to the RNaseE site at the 5Ј end of RNAI from pBR322 (29), can be separated readily. Moreover, this system can separate oligonucleotide substrates that differ only in the presence or absence of a monophosphate at the 5Ј end (data not shown).…”
Section: The Assay Of Rnasee By High Pressure Liquidmentioning
confidence: 99%
“…In the first study of this enzyme that used oligonucleotide substrates, it was found that a decaribonucleotide (ACAGU2AUUUG) corresponding in sequence to the single-stranded region at the 5Ј end of RNAI, the antisense regulator of ColE1-type plasmid replication, is cut at least as efficiently as the corresponding full-length transcript by RNaseE (29). It was subsequently found for the 9 S precursor of 5 S rRNA that the "a" site (ACAGA2AUUUG) but not the "b" site (AUCAA2AUAAA) is cut efficiently (17).…”
Section: Panel A)mentioning
confidence: 99%
“…The oligonucleotide BR13, containing the 13 nt single-strand sequence present at the 5Ј end of GGG.RNA I (McDowall et al, 1995), was labelled using T4 polynucleotide kinase (Life Technologies) (Sambrook et al, 1989) in the presence of [ 32 P0-␥]-ATP and was purified on urea-polyacrylamide gel (20%) (McDowall et al, 1995).…”
Section: Primer Extension Analysismentioning
confidence: 99%
“…Cleavage assays for RNase E activity RNA cleavage assays were performed at 30ЊC in 50 l reaction mixtures, as described in McDowall et al (1995), except that 4 U of ribonuclease A inhibitor (RNasin; Promega) was also added. Reaction mixtures contained 10 fmol of the 32 Plabelled RNA substrate (synthesized as described above) and the indicated amounts of enzyme.…”
Section: Primer Extension Analysismentioning
confidence: 99%